Une formulation numerique pour Ia caracterisation de Ia deformation des tissus composites par mise en forme - Billoe, Jean-Louis; Cherouat, A. Hakim (European Journal of Computational Mechanics, 2000)
High performance reinforced composite structures are generally obtained by shaping process. These reinforced composites are used in aeronautical and automotive industries. The proposed study concerns the simulation of the shaping process and permits to determine if the deformation operation is possible before manufacturing of tools. The numerical approach is proposed to model the behaviour of the prep reg woven fabric during the forming deformation. The global behaviour of composite fabric is modelled by a linear truss element system representative of warp and weft fibres behaviour and a isotropic elastic (or viscoelastic) membrane representative of resin behaviour. Comparisons with experiment results and simulations prove the efficiency of the proposed model.